In Defence of Holy Days: The Peasantry's Opposition to the Reduction of Holy Days in Early Modern Sweden. Issue 2 (October 2014) - Malmstedt, Göran
Abstract : During the early modern period most of the holy days celebrated in the late Middle Ages were abolished – although the rate of elimination varied between different confessions and areas. In comparison with other states, both Protestant and Catholic, the development in Sweden was characterized by a pronounced conservative tendency. This most likely reflects the views of the Swedish peasantry, as well as their ability to influence the course of events. My analysis of the peasantry's defence of holy days focuses on religious concerns and on the importance of a pre-modern worldview. Three interconnected motives are highlighted: the continuing cults of saints, the need for rituals to ensure the orderly behaviour of nature, and the conception of a contractual relationship with God and the resulting fear of God's wrath. Since the Swedish peasantry, along with most sections of society, continued to inhabit an enchanted world throughout the period, there was a strong need for methods of invoking heavenly support and fulfilling divine obligations. In finding their own ways of doing this, for example, by means of celebrating abolished holy days or the sanctifying of Saturdays, peasants demonstrated independence as well as a striking perseverance.